Improvement Automatic Diabetic Management System using Fuzzy Logic - Fahrul Nizar Novagusda (Fidelity : Jurnal Teknik Elektro, 2023)
In almost every nation on the planet, diabetes may be a common chronic condition. Monitoring blood glucose levels is essential to preventing diabetic complications and organ damage. The most used technique for monitoring blood glucose levels is intrusive, uncomfortable, expensive, and risky for transmitting infectious infections. The invasive procedure harms the tissues in the fingers over time. The suggested system functions on a diabetic patient and informs the caregiver or observer of the patient's state. The patient's fingertip is inserted between the glucose-measuring sensors, which a microcontroller uses to calculate the patient's glucose level. When the body's glucose level rises, an insulin injector will automatically inject insulin; glucose will be injected when it falls. The patient's mobile application is utilized to view the insulin and glucose injection amounts and the glucose measurements taken each time. When in critical condition, an SMS is sent to the doctor's or a family member's phone with crucial information and the patient's location.